A Comprehensive Review on Medicinal Importance of Cucumis melo - Yadav, Neha; Jangra, Pinki; Yadav, Kirti (Asian Journal of Pharmaceutical Research and Development, 2025)
Cucumis melo which is generally known as musk melon or Kharbuzah belongs to the family Cucurbitaceae. The plant is an annual climber or creeping herb characterized by its angular, scabrous stem, simple soft hairy orbicular-reniform leaves, and persistent tendrils that can be easily trained over trellises. The cultivation of musk melons is widespread throughout India, particularly, in the arid and thermally intense North-Western regions. Main components used include pulp, root, seeds, and seed oil. The compound has diuretic, emmenagogue, and cooling, demulcent effects. Throughout generations, fruit has been used to alleviate kidney problems including kidney and bladder stones, painful and burning urination, urinary tract ulcers, urinary retention, cough, hot inflammation of the liver, liver and bile blockage, dermatitis, and more. The oil extracted from seeds is highly nutritious and specifically contains linoleic acid (60-70%), lecithin, cephalin, and cerebroside. Melon seeds are composed of multiflorenol, isomultiflorenol, and 24-methylenecycloartenol esters. Its antimicrobial, antioxidant, antihyperlipidemic, anti-inflammatory, analgesic, diuretic, anthelmintic¸ nephroprotective and cytotoxic activity, Analgesic and Anti-inflammatory Activity, Anti-oxidant and free radical scavenging activity, Anti-Vitiligo Effect, Anti-ulcer activity, Anti-cancer activity, Hepato-protective activity, Diuretic effect, Protects against Hypothyroidism, Anti-diabetic activity, Haemagglutination and Haemolysis, Antibacterial and Anthelmintic activity, Antimicrobial activity, Antifungal, Nematicidal have been proved by research studies. Cucumis melo Linn., also known as melon, is a highly palatable and succulent fruit with a nutritional composition that provides vitamins A and C, potassium, and dietary fiber. Its health benefits include enhanced hydration and antioxidant qualities. Cucumis melo Linn. also holds significant economic significance, contributing to the agricultural economy by providing jobs and bolstering local markets. The species includes several cultivars, including cantaloupe and honeydew, each with unique taste profiles and textures. This variability highlights the importance of genetic variety in breeding initiatives to enhance yield resilience against pests and environmental stressors. Further research is needed to maximize the potential benefits of Cucumis melo Linn.